2020
DOI: 10.1074/mcp.ra119.001700
|View full text |Cite
|
Sign up to set email alerts
|

Citrullinome of Porphyromonas gingivalis Outer Membrane Vesicles: Confident Identification of Citrullinated Peptides

Abstract: Confident identification of citrullinated peptides. Abbreviations: (OMV) outer membrane vesicles, (WT) P. gingivalis W83 wild-type, (ΔPPAD) W83 knockout mutant of peptidyl arginine deiminase, (C351A) W83 expressing PPAD with the active site cysteine mutated to alanine, (2D) two-dimensional HFBA-based, (LC-MS) liquid chromatography mass spectrometry, (PAD) humane peptidyl arginine deiminase, (PPAD) bacterial P. gingivalis peptidyl arginine deiminase, (RA) rheumatoid arthritis, (PGE2) prostaglandin E2, (ACPA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Recent publications have shown that proteins carried on OMVs produced by P. gingivalis strain W83 can be citrullinated by PPAD and this included protein PG1881 (20). The data presented in this study demonstrate that when P. gingivalis cannot synthesize SLs, it was proficient in OMV biogenesis, yet the PG1881 protein is absent (or at low abundance) in the OMVs.…”
Section: Discussionmentioning
confidence: 49%
“…Recent publications have shown that proteins carried on OMVs produced by P. gingivalis strain W83 can be citrullinated by PPAD and this included protein PG1881 (20). The data presented in this study demonstrate that when P. gingivalis cannot synthesize SLs, it was proficient in OMV biogenesis, yet the PG1881 protein is absent (or at low abundance) in the OMVs.…”
Section: Discussionmentioning
confidence: 49%
“…gingivalis OMVs can be citrullinated (21). The data presented in this study show that when strain 381 cannot citrullinate peptides and/or proteins (Δppad mutant), the strain is deficient in OMV and biopearling biogenesis (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…7b). Taken together, these findings show that 381Δppad, which is unable to citrullinate substrates and its own proteins, demonstrates reduced proteolytic activity, which in turn makes (11,21). Given our findings that 381Δppad is deficient in the rate of proteolysis and forms a limited zone of hydration during the initial stage of surface translocation, we hypothesized that the secretion of T9SS cargo proteins via OMVs is impacted in the absence of PPAD.…”
Section: Downloaded Frommentioning
confidence: 68%
“…It was indicated in our previous study that the activity of citrullinating bacterial virulence factor-PPAD-had a certain importance during the formation of dual-species bacterial-fungal biofilm [16]. The modifications that PPAD introduces to diverse molecules play a role not only in relation to the functionality of bacterial proteins, and modulation of biofilm development, but also in the interactions with host proteins and systems [25,[66][67][68]. Under the conditions used in this study citrullination of such C. albicans proteins as glucan 1,3-beta-glucosidase Bgl2, elongation factor 1-alpha 1, Tdh3, heat shock proteins Ssa1 and Ssa2, yeast-form wall protein 1, plasma membrane ATPase 1, agglutinin-like sequence protein 3, 1,3-beta-glucanosyltransferase Pga4 and pH-responsive protein 1 was newly identified, whereas Eno1, Mp65, Adh1 and Eng1 were previously identified to be citrullinated [16].…”
Section: Discussionmentioning
confidence: 99%